Teacher Well-Being: Teachers’ Goals and Emotions for Students Showing Undesirable Behaviors Count More Than That for Students Showing Desirable Behaviors - Forster, Markus; Kuhbandner, Christof; Hilbert, Sven (Frontiers in Psychology, 2022)
Previous findings indicate that the goals of teachers and their experienced emotions when interacting with students play an important role for their well-being. However, studies on the psychological impact of events have shown that the impact of bad events is stronger than the impact of good events. Thus, it may be that teachers’ goals and emotions for students showing undesirable behaviors (e.g., students who disrupt the class, do not finish their work, have a negative attitude to learning) contribute more to their well-being than teachers’ goals and emotions for students showing desirable behaviors (e.g., students who pay attention in class, do their work on time, have a positive attitude to learning), a distinction that has not been made in previous research. To examine this question, we measured teachers’ goals and emotions for students showing desirable and undesirable behaviors, and their affective, evaluative, occupational, and psychological well-being (N = 250). The results showed that teachers’ well-being was relatively strongly related to their goals and emotions for students showing undesirable behaviors: The higher the goals and the more positive the emotions, the higher the reported well-being. By contrast, the goals and emotions for students showing undesirable behaviors were unrelated to teachers’ well-being. These results demonstrate that the principle of ‘bad is stronger than good’ holds also for the influence of teachers’ goals and emotions on their well-being.